“Quando entrei aqui era tudo mato [...] e agora se enxerga tudo vermelho de soja”: percepções acerca das transformações na paisagem em Cascavel/PR - Brocardo , Daniele (2020)
This research aims to analyse the perceptions concerning landscape transformations in Cascavel city – Paraná state. This transformations happened more intensly over the 1950s and the 1980s, mainly because of the presence of the wood industry and agriculture over the area. On the first chapter we carry out a bibliographical review aiming to map and analyse interpretations about these landscape transformations. On the second chapter we investigate the perceptions found in printed newspapers from Cascavel, from the years of 1960 to 1980. On the third chapter we analyse four Oral History interviews that were carried out between 2013 and 2018 with people who worked in activities from the wood industry and agriculture over the studied timeline. The interviewees are former agriculture workers and former wood industry employees. On the fourth and last chapter we focus on the photographic electronic collection from the Image and Sound Museum from Cascavel – MIS. This collection was first organized in 2009 by Cascavel city hall, alongside UNIOESTE – State University of Western Paraná. This research thesis is that these narratives – visual, written and spoken – present perceptions concerning Cascavel’s landscape transformations, which are connected to certain conceptions about the past, the present and the future of its territory and population. In most sources we found perceptions according to which the present is understood as something better, as a result of the transformations that happened in the local landscape, as the time of “progress and development”. However, we found out that there are, also, narratives that are different from those, narratives that see the landscapes of the past as something better, as a period of work, health and absence of agrochemicals etc. Therefore, Cascavel’s landscape transformations are analysed from different perceptions, which take into account the various people who lived them.